An improved method for the stilbenes synthesis via the heck reaction and approach to indole synthesis using pida / Ang Kheng Ping - Ang, Kheng Ping (2014)
Six iodoanilides incorporating different amide functionalities (e.g butyramide, furan carboxamide, cyclohexylamide, (2.1 to 2.6)) were prepared by established methods. These iodocarboxamides were transformed to the corresponding amido stilbenes (2.5 to 2.12) by an improved Heck procedure. Following silica gel chromatography, the resulting stilbene orthocarboxamides were exposed to diacetoxy iodobenzene with a view to indole synthesis.